Olgular Eşliğinde Genel Dahiliye - Acet, Aycan; Cırık, Salih; Çelikdelen, Selma Özlem; Gegin, Savaş; Özdemir, Burcu; Özdemir, Levent; Gezer, Deniz; Kavak, Hemrin; Sözen, Emine Sena; Ösken, Sibel; Akın, Ali; Doğantan, Şeyda; et al. (Academician Publishing Book DOI Portal, 2023)
-